Genome-Wide Analysis of Innate Susceptibility Mechanisms of Escherichia coli to Colistin - Muhammad Yasir; A. Keith Turner; Sarah Bastkowski; Martin Lott; Emma R. Holden; Andrea Telatin; Andrew J. Page; Mark A. Webber; Ian G. Charles (MDPI AG, 2022)
Colistin is an antibiotic that has seen increasing clinical use for the treatment of human infections caused by Gram-negative pathogens, particularly due to the emergence of multidrug-resistant pathogens. Colistin resistance is also a growing problem and typically results from alterations to lipopolysaccharides mediated by phosphoethanolamine (pETn) transferase enzymes which can be encoded on the chromosome, or plasmids. In this study, we used 'TraDIS-Xpress' (Transposon Directed Insertion site Sequencing with expression), where a high-density transposon mutant library including outward facing promoters in Escherichia coli BW25113 identified genes involved in colistin susceptibility. We examined the genome-wide response of E. coli following exposure to a range of concentrations of colistin. Our TraDIS-Xpress screen confirmed the importance of overexpression of the two-component system basSR (which regulates pETn transferases) but also identified a wider range of genes important for survival in the presence of colistin, including genes encoding membrane associated proteins, DNA repair machinery, various transporters, RNA helicases, general stress response genes, fimbriae and phosphonate metabolism. Validation experiments supported a role in colistin susceptibility for novel candidate genes tested. TraDIS-Xpress is a powerful tool that expands our understanding of the wider landscape of genes involved in response to colistin susceptibility mechanisms.